2013
DOI: 10.1371/journal.ppat.1003437
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Siderophores and Colibactin Genotoxin Biosynthetic Pathways in Escherichia coli

Abstract: In Escherichia coli, the biosynthetic pathways of several small iron-scavenging molecules known as siderophores (enterobactin, salmochelins and yersiniabactin) and of a genotoxin (colibactin) are known to require a 4′-phosphopantetheinyl transferase (PPTase). Only two PPTases have been clearly identified: EntD and ClbA. The gene coding for EntD is part of the core genome of E. coli, whereas ClbA is encoded on the pks pathogenicity island which codes for colibactin. Interestingly, the pks island is physically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
126
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 53 publications
(81 reference statements)
2
126
0
2
Order By: Relevance
“…This suggests that clbA could be expressed from a second promoter specifically activated under specific conditions of iron availability. This irondependent regulation of clbA transcription could constitute a fitness advantage for the bacteria, as we previously demonstrated that ClbA can also sustain siderophore biosynthesis (20).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This suggests that clbA could be expressed from a second promoter specifically activated under specific conditions of iron availability. This irondependent regulation of clbA transcription could constitute a fitness advantage for the bacteria, as we previously demonstrated that ClbA can also sustain siderophore biosynthesis (20).…”
Section: Discussionmentioning
confidence: 89%
“…S3). To yield pBAD33-T7-clbA, the 648-bp DNA sequence upstream of clbA in E. coli strain M1/5 (20), comprising the putative clbA promoter, the clbR gene, as well as the whole clbBR intergenic region (clbBR in. reg.…”
Section: Construction Of Venus Fusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colibactin induces senescence and consequent megalocytosis in cultured eukaryotic cells, which manifest as a progressive enlargement of the cell body and nucleus and the absence of mitosis. We quantified the extent of colibactin-induced megalocytosis using a methylene blue binding assay (12). E. coli strains were added to HeLa cells cultivated as described above at multiplicities of infection (MOIs) of between 12 and 400, cocultured for 4 h, and washed.…”
Section: Methodsmentioning
confidence: 99%
“…The 54-kb pks island encodes nonribosomal peptide synthases, polyketide synthases, and hybrid synthases, in addition to accessory, tailoring, and editing enzymes; the clbA gene encodes a phosphopantetheinyl transferase required for colibactin synthesis, and clbP specifies a D-amino peptidase involved in colibactin maturation (10,11). The pks island also contributes to the synthesis of siderophores by virtue of the broad substrate specificity of ClbA, impacting iron acquisition and the ability to survive in the blood compartment (12).…”
mentioning
confidence: 99%